Application of Picture Alphabet Calendar Media (KALFABER) Towards Literacy Skills of 4-5 Year Old Children in Kindergarten Bina Harapanku - Sitti Nur Lina; Sitti Nurhidayah Ilyas; Rika Kurnia R (Universitas Muhammadiyah Enrekang, 2024)
This study aims to determine the description of the Application of Picture Alphabet Calendar Media (KALFABER) to the Literacy Skills of 4-5 Year Old Children at Bina Harapanku Kindergarten. The type of research used is descriptive qualitative research. Research respondents were 1 teacher and 15 students. Data collection techniques using observation, interviews and documentation. Data analysis uses data reduction analysis, data presentation and verification. Based on the results of the study that after applying the pictorial alphabet calendar media (Kalfaber), children's literacy skills have developed very well. This proves that the pictorial alphabet calendar media (Kalfaber) can hone children's literacy skills such as the ability to recognize and mention letters, know the sound of the initial letter and can distinguish between letters, distinguish animal sounds from surrounding objects, read syllables and match words with pictures and read words and match words with pictures.